2021
DOI: 10.1186/s12875-021-01504-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of training healthcare professionals’ communication skills on the clinical care of diabetes and hypertension: a systematic review and meta-analysis

Abstract: Background Diabetes and hypertension care require effective communication between healthcare professionals and patients. Training programs may improve the communication skills of healthcare professionals but no systematic review has examined their effectiveness at improving clinical outcomes and patient experience in the context of diabetes and hypertension care. Methods We conducted a systematic review of randomized controlled trials to summarize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
0
15
2
2
Order By: Relevance
“…Communication skills training for GPs in China should ensure that such areas are addressed, and patient tools and communication aids may further facilitate these conversations. Communication of this type must also offer a tailored discussion, adapting to the particular risk profile of the patient and providing relevant management advice that takes the patient perspective into account [ 17 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Communication skills training for GPs in China should ensure that such areas are addressed, and patient tools and communication aids may further facilitate these conversations. Communication of this type must also offer a tailored discussion, adapting to the particular risk profile of the patient and providing relevant management advice that takes the patient perspective into account [ 17 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This qualitative focus group study is part of a programme of research, aimed to understand the communication experiences in type 2 diabetes care in China, and related training needs. A review of the literature highlighted the importance of effective communication between healthcare providers and diabetes patients to ensuring optimal diabetes care [ 15 – 17 ]. Also, the patient–provider relationship has a strong bearing on patients’ adherence to treatment [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Key elements for successful communication training were identified including teaching theories, appropriate training content, and training methods. Research gaps in communication skills training for diabetes care were identified in this systematic review: training needs to understand what health professionals and patients’ thoughts and goals should be based on encouraging patients to self-manage and shared understanding of diabetes management [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Attempts to cover this breadth within a training curriculum risks a superficial approach to a complex phenomenon, where knowing ‘where to start’ may be difficult. Our systematic review suggested that such that ‘one size fits all’ approaches to communication skills training should be exercised with caution [ 23 ]. Furthermore, the training of communication skills for Chinese GPs may represent a paradigm shift in learning and patient care, which could be overwhelming for many learners, risking disinterest or disengagement.…”
Section: Introductionmentioning
confidence: 99%
“…En el Cuadro 4 se presentan algunas barreras, facilitadores y estrategias de implementación que pueden ser consideradas por los países. (16,20,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) CUADRO 4. Barreras, facilitadores y estrategias para mejorar el cumplimiento de las recomendaciones…”
Section: Conclusionesunclassified